2001
DOI: 10.1016/s0167-2789(01)00306-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of disorder on the fracture nucleation process

Abstract: The statistical properties of failure are studied in a fiber bundle model with thermal noise. We show that the macroscopic failure is produced by a thermal activation of microcracks. Most importantly the effective temperature of the system is amplified by the spatial disorder (heterogeneity) of the fiber bundle. The case of a time dependent force and the validity of the Kaiser effects are also discussed. These results can give more insight to the recent experimental observations on thermally activated crack an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
91
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 25 publications
7
91
3
2
Order By: Relevance
“…Based on the analysis of a simple fiber bundle rupture model, Refs. [3,4] showed that the average lifetime of the fiber-bundle takes an Arrhenius form with an effective temperature renormalized from the bare temperature T to a value strongly amplified by the presence of the frozen disorder in the rupture thresholds f c (i), in agreement with experiments and numerical simulations. This result suggests that the usual assumption of neglecting the role of thermal fluctuations in material rupture processes at room temperature may actually be incorrect (see [5] for early discussions): due to frozen heterogeneities, tiny thermal fluctuations can be amplified many times, thus actually controlling the time-dependent aspects of failure.…”
supporting
confidence: 61%
See 4 more Smart Citations
“…Based on the analysis of a simple fiber bundle rupture model, Refs. [3,4] showed that the average lifetime of the fiber-bundle takes an Arrhenius form with an effective temperature renormalized from the bare temperature T to a value strongly amplified by the presence of the frozen disorder in the rupture thresholds f c (i), in agreement with experiments and numerical simulations. This result suggests that the usual assumption of neglecting the role of thermal fluctuations in material rupture processes at room temperature may actually be incorrect (see [5] for early discussions): due to frozen heterogeneities, tiny thermal fluctuations can be amplified many times, thus actually controlling the time-dependent aspects of failure.…”
supporting
confidence: 61%
“…(B11) in [3]), which shows that, for Φ > Φ * , the failure rate accelerates towards a finite-time singularity approximately as ∼ 1/(t c − t). Such a behavior has been documented extensively in experiments on rupture of heterogeneous material [6].…”
mentioning
confidence: 89%
See 3 more Smart Citations